Ratio Legis Tanggung Jawab Sosial dan Lingkungan Perusahaan dalam Menuju Harmoni Interaksi Perusahaan, Pemerintah dan Masyarakat - Deswina Maharani, Citra Ayu; Arifudin, Nur; Kurahman, Fauzi; Galih Ray Alfaries, Muhammad (Universitas Ekasakti, 2024)
Corporate Social Responsibility (CSR) is a concept that states an organization (Company) has a responsibility towards consumers, employees, shareholders, communities and the environment in all aspects of the company's operations. For example, regarding problems that impact the environment, such as pollution, waste, product safety and labor. Based on Positive Law